2019
DOI: 10.1111/1750-3841.14592
|View full text |Cite
|
Sign up to set email alerts
|

Structures and In Vitro Antihepatic Fibrosis Activities of Prenylated Dihydrostilbenes and Flavonoids from Glycyrrhiza uralensis Leaves

Abstract: Glycyrrhiza uralensis is the major plant source of licorice. This study was to identify bioactive compounds from the plant's leaves in order to make better use of its aerial part. An ethanol extract of the leaves was subjected to repeated chromatography to yield 15 compounds. The structures were determined to be three novel dihydrostilbenes, based on their various spectroscopic data-glycypytilbene A (1), glycydipytilbene (2), and glycypytilbene B (3)-and 12 known compounds, α,α -dihydro-3,5,4 -trihydroxy-4,3 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Compound 6 showed the [M + H] + peak at m/z 533.1656 (calcd for C 26 H 29 O 12 , 533.1659), which established a molecular formula of C 26 H 28 O 12 , indicating that it was a glycosylated derivative of 2. Presence of the sugar moiety was confirmed by the additional proton and carbon signals (δ H 5.02 and 3.19-3.68 (6H); δ C 100.3, 77.5, 76.8, 73.5, 69.9, 61.0) observed in the 1 H and13 C NMR of 6. The sugar was assigned to be a glucopyranose on the basis of NMR data and by comparison of the TLC R f value with that of the d-glucose reference standard after acidic hydrolysis of 6.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Compound 6 showed the [M + H] + peak at m/z 533.1656 (calcd for C 26 H 29 O 12 , 533.1659), which established a molecular formula of C 26 H 28 O 12 , indicating that it was a glycosylated derivative of 2. Presence of the sugar moiety was confirmed by the additional proton and carbon signals (δ H 5.02 and 3.19-3.68 (6H); δ C 100.3, 77.5, 76.8, 73.5, 69.9, 61.0) observed in the 1 H and13 C NMR of 6. The sugar was assigned to be a glucopyranose on the basis of NMR data and by comparison of the TLC R f value with that of the d-glucose reference standard after acidic hydrolysis of 6.…”
mentioning
confidence: 89%
“…Thus, metabolite 5 was assigned as 8-prenylquercetin 3-O-β-d-glucopyranoside. 13 C NMR of 6. The sugar was assigned to be a glucopyranose on the basis of NMR data and by comparison of the TLC R f value with that of the d-glucose reference standard after acidic hydrolysis of 6.…”
Section: Structure Elucidation Of Metabolites Of Prenylquercetinsmentioning
confidence: 99%
See 2 more Smart Citations
“…against the gastric adenocarcinoma (SGC-7901) cell line with IC 50 values in the range of 8.7 to 64.9 μ g/mL for different compounds. Moreover, Fan et al [ 125 ] identified the biologically active components of Glycyrrhiza uralensis Fisch. leaves and noted that most of these compounds exhibited an antiproliferative effect on human hepatic stellate cells with IC 50 values in the range of 43 to more than 90 μ g/mL for different compounds.…”
Section: Biological Activitiesmentioning
confidence: 99%